PENERAPAN MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION (GI) BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR IPS (Studi pada Siswa Kelas VIII SMP Nahdlatuth Thalabah) - Winda Hurotul'Aini; Priangga Eko (Nusantara Hasana Berdikari, 2022)
Learning is an effort made by each individual. Learning with group investigation is learning that emphasizes that students must learn by finding information on their own. The teacher conveys material with only important points and provides opportunities for students to develop and explore the material. The learning objectives with group investigation are a. Assist students in investigating a topic systematically and analytically. This has positive implications for developing discovery skills and helping to achieve goals. b. In-depth understanding of a topic carried out through investigation. c. Group Investigation trains students to work cooperatively in solving a problem. The research model used in this research is Classroom Action Research which is included in qualitative research. This research was carried out in collaboration between classroom teachers, researchers, and involving students. Based on the research that has been carried out, it can be concluded that there is an increase in social skills and student learning outcomes which are only 55% increased to 88%.